Hell followed with us - White, Andrew Joseph (Peachtree Teen, 2022)
"Sixteen-year-old trans boy Benji is on the run from the cult that raised him--the fundamentalist sect that unleashed Armageddon and decimated the world's population. Desperately, he searches for a place where the cult can't get their hands on him, or more importantly, on the bioweapon they infected him with. But when cornered by monsters born from the destruction, Benji is rescued by a group of teens from the local Acheson LGBTQ+ Center, affectionately known as the ALC. The ALC's leader, Nick, is gorgeous, autistic, and a deadly shot, and he knows Benji's darkest secret: the cult's bioweapon is mutating him into a monster deadly enough to wipe humanity from the earth once and for all. Still, Nick offers Benji shelter among his ragtag group of queer teens, as long as Benji can control the monster and use its power to defend the ALC. Eager to belong, Benji accepts Nick's terms... until he discovers the ALC's mysterious leader has a hidden agenda, and more than a few secrets of his own"--Dust jacket flap.